Hubungan Lama Paparan Layar Komputer dengan Kelelahan Mata pada Staf Tata Usaha Universitas Muhammadiyah Surakarta - Devia Nadia Kirana; Sri Darnoto (JUKEJ : Jurnal Kesehatan Jompa, 2026)
The use of computers in daily work activities makes administrative staff a group vulnerable to experiencing eye fatigue. Eye fatigue is one of the occupational health problems that can affect comfort, concentration, and work productivity. This study aimed to analyze the relationship between the duration of computer screen exposure and eye fatigue among administrative staff at Campus 1 Universitas Muhammadiyah Surakarta. This quantitative used a cross-sectional design and involved 54 respondents selected through total sampling. Data were collected using the Visual Fatigue Index (VFI) questionnaire and analyzed using the Chi-Square test followed by Fisher’s Exact test. The result showed no significant relationship between the duration of computer screen exposure and eye fatigue (p=0,669). However, respondents with longer exposure tended to experience eye fatigue more frequently. The duration of screen exposure is not the only factor influencing eye fatigue, therefore attention to other contributing factors is necessary to maintain the visual health of administrative staff